Handwashing with Soap Counseling (CTPS) on Children's Knowledge and Attitudes in the Era of the Covid-19 Pandemic - Idris Idris; Andi Nursiah; Isymiarni Syarif; Yanti Latif (Jurnal Ilmiah Kesehatan (JIKA), 2022)
Knowledge about handwashing is important as an effort to prevent Covid-19 in children. The purpose of this study is to determine the effect of handwashing with soap (CTPS) counseling on children's knowledge and attitudes in the era of the Covid-19 pandemic. This research was designed as a quasi-experimental approach with a pre-test,post test group design approach. The sampling technique used was purposive sampling. The sample for the study consisted of children aged 12 to 14 years, for a total of 30 people.The instrument used was a questionnaire with a meter using the Guttman scale. The data were analyzed using a statistical test (Wilcoxon test). The results of this study showed that based on the statistical test results of the ranking test signed by Wilcoxon, a p-value = 0,000 was obtained, which means that the p value is less than 0,05. There was an effect of counseling on handwashing with soap (CTPS) on the knowledge and attitudes of MTS class VII students. Based on the discussion, it can be concluded that there was an effect of hand washing counseling on the hand washing attitude and knowledge. Therefore, students should apply hand washing with soap (CTPS) in preventing the transmission of Covid-19.